Synthesis of polydimethylsiloxane microspheres using microfluidics for treatment of Toluene in Wastewater - Lian, Zheng; Ren, Yong; He, Jun; Chen, George Z.; Koh, Kai Seng (ASME, 2018)
Monodispersed polydimethylsiloxane (PDMS) microspheres are fabricated by a needle-based versatile microfluidic device with flow-focusing geometry. Microdroplets with various diameters are generated by tuning the flow rate of the dispersed and continuous phase, using single emulsion as the template. The collected PDMS microdroplets are then thermally cured to form solid microspheres. We employ an optical microscope to observe the particles and capture photos. The figures are processed by ImageJ which measures the diameter of each particle. The coefficients of variation (CV) of particles are found to be less than 1.5% for all sizes, indicating that a high monodispersity has been achieved. Thereafter, we adopt the PDMS microspheres to a simulated industrial wastewater that contains organic pollutant such as toluene, for removing purposes. Since the solubility parameters of PDMS and toluene are close, toluene molecules can be extracted from its solvent into PDMS. The absorption efficiency provided by PDMS microspheres on organic pollutant such as toluene has been tested by utilizing a Headspace-Gas Chromatography (GC-HS). We then compare the obtained peak signals of toluene before and after treatment to verify the treatment effect. The needle-based microfluidic device is advantageous in its facile assembly and low cost, displaying a great potential for industrial applications.